2023
DOI: 10.1002/cb.2170
|View full text |Cite
|
Sign up to set email alerts
|

How to arrange assortments available in green alternatives: Displaying products by green attributes

Abstract: Previous research has investigated how product display affects consumer choices.However, less is known about the effect of product display on green consumption when products are displayed by green attributes. Through three studies with 610, 661, and 208 valid participants, respectively, the present research demonstrates that displaying products by green attributes render green products more recognizable to the consumer, thereby inducing green choices from among the consideration sets.The positive effect is enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…For instance, in terms of display forms, Wang et al (2020) found that when consumers are psychologically distant from environmental issues, upward displays of eco-friendly products can improve their processing fluency of product information, resulting in more favorable product evaluations and higher purchase intentions (Xiao et al, 2023) showed that perceived greenness was higher for environmentally friendly products with low visual density design. In addition, regarding the display environment, Yao (2023) demonstrates that displaying products with green attributes renders green products more recognizable to the consumer, thereby inducing green choices among the consideration sets. Rizzi et al (2022) found that touchpoints influence consumers' perceptual consistency, influencing their purchasing decisions for green products.…”
Section: Green Productmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, in terms of display forms, Wang et al (2020) found that when consumers are psychologically distant from environmental issues, upward displays of eco-friendly products can improve their processing fluency of product information, resulting in more favorable product evaluations and higher purchase intentions (Xiao et al, 2023) showed that perceived greenness was higher for environmentally friendly products with low visual density design. In addition, regarding the display environment, Yao (2023) demonstrates that displaying products with green attributes renders green products more recognizable to the consumer, thereby inducing green choices among the consideration sets. Rizzi et al (2022) found that touchpoints influence consumers' perceptual consistency, influencing their purchasing decisions for green products.…”
Section: Green Productmentioning
confidence: 99%
“…Green perceived value refers to the value consumers derive from green products in favor of environmental sustainability. Specifically, it refers to the role of products in saving resources, environmental protection, and improving consumers’ awareness of eco-friendly practices (Riva et al, 2022; Roh et al, 2022; Yao, 2023).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations